Segmentasi dan Positioning Jasa Pendidikan di MAN Yogyakarta III - Atika, Atika; machali, imam (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
This research discusses about the segmentation and the position of education servicesin order to determine its implementation in Islamic Educational Institutions. This is aqualitative research with the primary respondent for all the school community who areinvolving in the marketing process. This research used phenomenological approach,while the data was collected using observation method, indepth interviews,documentation and triangulation. The results indicates that: (1) MAN Yogyakarta IIIdefines market segmentation by applying multiple segmentation approach, namely: (a)demographic segmentation, (b) geographic segmentation, (c) psychographicsegmentation, (d) psychological segmentation, and (e) benefit segmentation. (2) MANYogyakarta III determines the position of educational services in the academic fieldwith the development of the brand “Madrasah of The Champions” that leads to thevision of MAYOGA, namely Ultraprima. Market segmentation is the first thing thatmust be accomplished by the madrasah to achieve optimum marketing results, followedby positioning. Position or image formed by the institutions has a dominant role ininfluencing public attitudes toward madrasah.